AS-SUNNAH SEBAGAI SUMBER HUKUM ISLAM DALAM ERA YANG PROBLEMATIK - Laila Lailatul Qodriyyah; Yuhana Rizki Farista; Zulham Maula Farid (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2021)
As-Sunnah or what we often call Sunnah is the plural form of the word sunan which means